Reorientasi Kajian Teologi Islam: Ikhtiar Kontributif Atasi Problem Kekinian - Muhammad Rusli (Universitas Islam Negeri Mataram, 2012)
The central issue in the study of classical Islamic theologians is closely linked with their surrounding context challenging them at the time. One of the basic problems is the incessant spread of Greek philosophy and elements of non Islamic teachings involved in the struggle of Islamic thought at the time, so that the theologians found it corrupting the Islamic faith. The study of Islamic theology at the time, therefore, was aimed at anticipating the destruction of Islamic values. Philosophical values of the movement should inspire contemporary theologians to resolve the various problems faced by the muslim communities. Therefore, contemporary study of Islamic theology should not dwell on the issues of “heavens” and be busy of “defending the God”. It should go further into the solution to the problem of the muslim people and human in general today.